When and how cognitive conflict benefits cross-functional project team innovation: The importance of knowledge leadership. Issue 4 (12th August 2019) - Guo, Haiyan; Zhang, Lianying; Huo, Xiaoyan; Xi, Guannan
Abstract : Purpose: This research aims to comprehensively investigate when and how cognitive conflict benefits team innovation in cross-functional project teams (CFPTs), by exploring the moderating role of knowledge leadership and dual mediation mechanisms of elaboration of task-related information/knowledge and affective conflict. Design/methodology/approach: All hypotheses have been empirically tested by using structural equation model to analyze the quantitative data from a questionnaire survey covering 73 CFPTs in China. Findings: Results indicate that knowledge leadership positively moderates the relationship between cognitive conflict and CFPT innovation. This moderating effect is directly or indirectly revealed by the dual mediating roles of task-related information/knowledge elaboration and affective conflict, which are two processes manifesting whether cognitive conflict can or cannot be incorporated into team innovation. Research limitations/implications: Despite the external validity of results limited by convenient sampling method, the findings offer implications for promoting CFPT innovation. This can be achieved by developing competent knowledge leadership into team sensegiver, dissent reconciler and facilitator to accentuate benefits of cognitive conflict in information/knowledge elaboration and attenuate the likelihood of escalating to affective conflict. Originality/value: This study advances the understanding of why cognitive conflict has an equivocal effect on team innovation in the context of CFPT by originally revealing how leaders' role in information/knowledge management acts as a contingency and suggesting the dual mediating mechanisms that reflect the contingent impact. Project-based teams or organizations, characterized by cognitive clashes, can enhance innovation performance by shaping the meaningfulness of information/knowledge activities triggered by cognitive conflict.